PENYUSUNAN LAPORAN KEUANGAN PADA ORGANISASI KEAGAMAAN BERDASARKAN ISAK NO 35 (Studi Kasus Masjid Agung Jami Singaraja): (Studi Kasus Masjid Agung Jami Singaraja) - Ainisuh Nurfaisyah; Nyoman Trisna Herawati (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the process of preparing financial statements prepared by Agung Jami Mosque, the obstacles faced in the preparation of financial statements based on ISAK No. 35 and the process of preparing financial statements of Agung Jami Mosque based on ISAK No. 35. The design of this research was qualitative descriptive with data sources, data collection and data analysis techniques. The results of the study shows that the process of preparing the financial statements of Agung Jami Mosque is quite simple, which only includes cash income and expenditure. The obstacle faced in preparing the financial statements of Agung Jami Mosque is the lack of human resources in the field of accounting. The financial statements of Agung Jami Mosque which are prepared based on ISAK No. 35 are in the form of statements of financial position, statements of comprehensive income, reports of changes in net assets, statements of cash flows and notes. on financial statements. The total of statement of financial is Rp 2,812,983,672, the comprehensive report shows a balance of Rp 16,143,736, the statement on changes in net assets shows a balance of Rp 2,812,983,672, the cash flow statement shows a balance of Rp 46,681,286 and notes to the financial statements.